ANALISIS POLA KOMUNIKASI ORANG TUA DAN TEMAN SEBAYA TERHADAP PERKEMBANGAN SOSIAL ANAK USIA DINI (STUDI KASUS DI TK RINJANI UNRAM) - Nurholiza Izzati; Ida Ermiana; Darmiany (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Parental and peer communication patterns play a crucial role in shaping early childhood social development. This study aims to analyze the forms of communication patterns between parents and peers and their influence on the social development of early childhood at TK Rinjani UNRAM. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews with parents and teachers, and documentation. The data analysis technique used an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that democratic and open communication patterns between parents and children foster positive social behaviors such as cooperation, empathy, and self-confidence. Meanwhile, peer communication patterns that emphasize interaction, collaboration, and mutual respect significantly support children's social development. The study concludes that harmonious communication between parents and peers contributes positively to the social development of early childhood. These findings are expected to provide insights for parents, educators, and schools in optimizing communication strategies to support children's social growth